Cross‐reactivity of hepatitis C virus specific vaccine‐induced T cells at immunodominant epitopes. Issue 1 (30th October 2014) - Kelly, Christabel; Swadling, Leo; Brown, Anthony; Capone, Stefania; Folgori, Antonella; Salio, Mariolina; Klenerman, Paul; Barnes, Eleanor
<x xml:space="preserve">Abstract</x> Viral diversity is a challenge to the development of a hepatitis C virus (HCV) vaccine. Following vaccination of humans with adenoviral vectors, we determined the capacity of T cells to target common viral variants at immundominant epitopes ex vivo. We identified two major variants for epitopes NS31073 and NS31446, and multiple variants for epitope NS31406 that occurred in >5% of genotype 1 and 3 sequences at a population level. Cross‐reactivity of vaccine‐induced T cells was determined using variant peptides in IFN‐γ ELISPOT assays. Vaccine‐induced T cells targeted approximately 90% of NS31073 genotype 1 sequences and 50% of NS31446 genotype 1 and 3 sequences. For NS31406, 62% of subtype‐1b sequences were targeted. Next, we assessed whether an in vitro priming system, using dendritic cells and T cells from healthy donors, could identify a variant of NS31406 that was maximally cross‐reactive. In vitro priming assays showed that of those tested the NS31406 vaccine variant was the most immunogenic. T cells primed with genotype 1 variants from subtype 1a or 1b were broadly cross‐reactive with other variants from the same subtype. We conclude that immunization with candidate HCV adenoviral vaccines generates cross‐reactive T cells at immunodominant epitopes. The degree of cross‐reactivity varies between epitopes and may be HCV‐subtype specific.